The Characteristics of Land‐Atmospheric Water and Heat Exchange during Soil Freezing‐Thawing Process over the Underlying Surface of the Alpine Grassland in the Source Region of the Yellow River - Yueyue WU; Jun WEN; Zuoliang WANG; Dongyu JIA; Wenhui LIU; Yuqin JIANG; Xuancheng LU (Gaoyuan qixiang)
The seasonal characteristics of water and heat exchange in the alpine grasslands are significant， and the freezing‐thawing process has an important impact on the land‐atmospheric water and heat exchange.Based on the observation data of the land surface process in the Tangchama small watershed in the source area of the Yellow River from May 2014 to May 2015， this research divides the soil freezing‐thawing process into thawed stage （TT）， frozen stage （FF）， thawing to freezing （T-F） and freezing to thawing （F-T）， and the changes in the different states and period of the net radiation， sensible heat flux， latent heat flux and surface heat flux of the underlying surface of the alpine grassland are analyzed to explore the characteristics of water and heat exchange between the land‐atmosphere in the soil freezing‐thawing process.The results are as follows： （1） The average value of the net radiation flux in the thawed stage is generally greater than that of the other three stages， and the maximum value reaches 203.7 W·m-2.The frozen soil melts in the freezing‐thawing stage， and the soil moisture content gradually increases.The radiation ratio increased significantly during the frozen stage， the net radiation diurnal variation was the largest in the thawed stage， reaching 717.6 W·m-2， and the frozen stage was the smallest， followed by the freezing‐thawing stage.（2） The proportion of sensible heat flux and latent heat flux is different in the thawed and frozen stages.When completely thawed， due to precipitation and soil moisture content， the net radiation is mainly converted into latent heat flux.The maximum diurnal variation of latent heat flux is 193.7 W·m-2， while the sensible heat flux is only about 80.0 W·m-2.The diurnal average of sensible heat and latent heat in the thawing‐freezing phase， the freezing‐thawing period and the frozen period is not much different.The mean latent heat in the three period is 21.9 W·m-2， and the sensible heat is 20.3 W·m-2； The diurnal variation is greater than the latent heat in the three period， the soil suffers a freezing‐thawing cycle， the soil temperature difference is small， and the water content changes， and the net radiation is mainly converted into sensible heat during this period； the diurnal variation of sensible heat was greater than that of latent heat in the three stages.The freezing-thawing cycle occurred in the soil， the difference between ground and air temperature was small， and the moisture content changed.During this period， the net radiation was mainly converted to sensible heat.（3） The soil heat flux is positive （negative） in thawed （frozen） state， indicating that the surface soil absorbs （releases） heat from the atmosphere， and its daily variation range is large （small）.The above results show that the state and process of soil freezing and thawing have different characteristics for the water and heat exchange process between the land and atmosphere.